Penerapan Metode Cooperative Integrated Reading and Composition (CIRC) Untuk Meningkatkan Hasil Belajar Siswa Kelas IV-A Pada Mata Pelajaran Fiqih Pokok Bahasan Infak dan Sedekah Di MI. Tarbiyatul Islamiyah Tenggur Rejotangan Tulungagung - Balqis Fauzatul Rohmah (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
Studies Fiqh very important to lead all activities in this life, be it the relationship between man and the Creator and fellow human beings. To understand all the science, particularly on the subjects of jurisprudence cannot be separated from the act of reading. One of the methods that implement activities that read and activities to socialize are a method of Cooperative Integrated Reading and Composition (CIRC). The main purpose of using CIRC in learning is to increase reading interest of students, help students improve reading comprehension, and improve learning outcomes is low. Objectives: 1) To determine the application of methods Cooperative Integrated Reading and Composition (CIRC) on the subjects of Fiqh subject Infak and Sedekah grade IV-A at Islamic Elementary School Tarbiyatul Islamiyah Tenggur Rejotangan Tulungagung. 2) To know the improvement of learning outcomes of students of class IV-A with the adoption of Cooperative Integrated Reading and Composition (CIRC) on the subjects of Fiqh subject Infak and Sedekah in Islamic Elementary School Tarbiyatul Islamiyah Tenggur Rejotangan Tulungagun. This research was conducted at the Islamic Elementary School Tarbiyatul Islamiyah Tenggur Rejotangan Tulungagung in March 28 to April 29, 2015. This type of research is classroom action research using two cycles of action. Each cycle includes planning, implementation, observation, and reflection. The subjects of this study were students of class IV-A with 17 students consisting of 8 boys and 9 girls. Learning process using teaching methods Cooperative Integrated Reading and Composition (CIRC). Methods of data collection using observation, testing, observation, interviews, documentation and field notes. Mastery learning students achieved if the student received grades of 70 or more. Results of the study are: the results of post-test on the first cycle and second cycle that mentions the existence of the progressive increase learning outcomes. Originally the average value of the initial test (pre-test) 66.47 and the posttest cycle I the average value to 70 with learning completeness percentage of 70.58%, which means that the learning completeness percentage is still below the minimum completeness criteria that have been determined, is 75%. In the next cycle, the second cycle there is an increase in learning outcomes with the average value becomes 82.23. Percentage on mastery learning students in the second cycle already meet the completeness criteria predetermined, is 100%